Pengaruh Work Life Balance Dan Work Stress Terhadap Turnover Intention Dengan Job Satisfaction Sebagai Variabel Mediasi Pada Karyawan BPR Di Indonesia - Risma Indriyani; Helmi Buyung Aulia Safrizal (Jurnal Kajian Ilmu Manajemen (JKIM), 2026)
This study aims to analyze the influence of work life balance and work stress on turnover intention with job satisfaction as a mediating variable in BPR employees in Indonesia. The phenomenon of employee turnover is a strategic problem in the banking sector, including BPR in Indonesia. The high level of employee turnover has an impact on increasing operational costs and disrupting organizational stability. This study uses a quantitative approach with an explanatory research type. This study used a sample of 150 BPR employees, selected using a purposive sampling technique. Data collection was carried out through a questionnaire with a Likert scale, and data analysis used the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method with the help of SmartPLS 4.1 software. The results of the study indicate that work life balance has a significant negative effect on turnover intention, work stress has a significant positive effect on turnover intention, work life balance has a significant positive effect on job satisfaction, work stress has a significant negative effect on job satisfaction, and job satisfaction has a significant negative effect on turnover intention. Job satisfaction is proven to act as a partial mediating variable in the relationship between work life balance and work stress on turnover intention. This study provides practical implications for BPR management to maintain and improve employee work life balance, manage work stress, and improve job satisfaction as an effective employee retention strategy.